FORMATION OF SPIRITUAL AND MORAL QUALITIES OF FUTURE TEACHERS (American Journal of Pedagogical and Educational Research, 2023)
Training future teachers is an important task of the field of pedagogy. This article talks about the theoretical foundations of the formation of spiritual and moral qualities of future teachers.